TINJAUAN SISTEMATIS PERAN KECERDASAN BUATAN DALAM PENGUATAN KUALITAS PENGUNGKAPAN ESG DAN KONSTRUK AUTENTISITAS, KEPERCAYAAN, SERTA LOYALITAS KONSUMEN DI PASAR EMERGING - Lumban Tobing, Boni Benyamino (JURNAL ILMIAH EDUNOMIKA, 2025)
This systematic literature review examines the evolving role of Artificial Intelligence (AI) in strengthening the quality, transparency, and credibility of Environmental, Social, and Governance (ESG) disclosures in contemporary sustainability reporting. Drawing on 35 peer-reviewed Scopus Q1/Q2 articles published between 2020 and 2025, the review synthesizes current evidence on how AI supports anomaly detection, automates data processing, enhances verifiability, and mitigates greenwashing practices. The findings reveal five major thematic insights: (1) AI substantially improves the accuracy and consistency of ESG disclosure; (2) AI-enabled linguistic and anomaly-based models are effective in detecting misleading sustainability claims; (3) digital transparency supported by AI strengthens perceived authenticity of corporate sustainability efforts; (4) the credibility of AI-processed ESG information enhances stakeholder trust by reducing informational risk; and (5) AI-enhanced authenticity and trust positively influence consumer responses, including green attitudes, loyalty, and sustainable purchase intentions. This study highlights persistent gaps in the integration of AI governance, ethics, and cross-market applications, especially in emerging economies. The review contributes an evidence-based conceptual synthesis for understanding the mechanisms through which AI reinforces sustainability communication and suggests directions for future empirical research. Keywords: Artificial Intelligence; ESG Disclosure; Greenwashing Detection; Authenticity; Stakeholder Trust